A survey of flood disaster preparedness among hospitals in the central region of Thailand - Rattanakanlaya K. (2017)
© 2016 College of Emergency Nursing Australasia Background In 2011, Thailand was affected by the one of the worst flood disasters in recent times. Hospitals in Thailand were faced with the challenge of managing the health impacts from this natural disaster. The purpose of this study was to assess flood disaster preparedness among hospitals in the central region of Thailand. Methods A survey questionnaire was given to twenty-seven key people responsible for hospital disaster preparedness that experienced disruptions to health services (severely, moderately and slightly) during the flood disaster in 2011 in the central region of Thailand. Results Of the twenty-four participating hospitals, not one had satisfied the standards in all the dimensions of flood disaster preparedness. All respondent hospitals were deficiently prepared with regard to surge capacity, the management of healthcare services and the management of the supporting systems. The availability of supplies and equipment were found to be in place but preparations were found to be inadequate in organizing staff at all participating hospitals. Trained staff members regarding disaster response were reported to be present in all respondent hospitals. Hospitals that experienced slightly disruptions to their health services did not elect to do any exercises to meet the set standards. None of the hospitals that experienced slightly disruptions to their health services performed any evaluation and improvement in terms of disaster preparedness. Conclusions Many hospitals were not up to standard in terms of disaster preparedness. Hospitals should prioritize disaster preparedness to fulfill their responsibility during crisis situations and improve their flood disaster preparedness.